Health communication and the digital divide : covid-19 amongst senior citizens in Soweto, Gauteng Province - Chauke, Vukosi (My University, 2024)
During the pandemic, 80% of COVID-19 cases reported were amongst the elderly population, with the history of digital divide amongst the population. In the same vein, because of its segregationist history South Africa remains the most unequal country in the whole world, with a Gini-coefficient amounting to 0.63. This research aimed to investigate how lack of access to digital communication tools, used for health communication campaigns, affected the elderly during the COVID-19 pandemic among senior citizens in Soweto, Gauteng. The population of the study included senior citizens and the data were analysed through thematic analysis and revealed that the attitude towards ICTs played the most significant role in preventing senior citizens to gain access to COVID-19 information through technological means, and that information was obtained through physical social networking and traditional mainstream media. Despite their familiarity with the COVID-19 regulations, most senior citizens did not comply with the COVID-19 regulations put in place, particularly shopping activities. There are low e-commerce engagement activities among senior citizens, most of them are shopping the traditional way. The study recommends that a similar study be conducted on a different population group. The government must build trust with citizens. Trust must be the basis of every relationship; this will make it easier for citizens to accept health communication.
Thesis (M. Communication Studies) -- University of Limpopo, 2024
Keywords: Health communication; Digital divide; Senior citizens; Covid-19; Gauteng Province; COVID-19 (Disease); Older people; Digital divide -- South Africa; Communication in public health